Listen to the wind : the story of Dr. Greg and Three cups of tea - Mortenson, Greg.; Roth, Susan L. (New York, N.Y. : Dial Books for Young Readers, 2009)
Relates the story of Greg Mortenson and how he lost his way coming down from K2 in the mountains of Pakistan, and found a poor village and his life work.
Includes bibliographical references.
Keywords: Rural schools -- Pakistan -- Juvenile literature